Bad moon rising - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- Dark-hunter novel., 2009)
When war erupts among the lycanthropes, Fang Kattalakis, the brother of two of the most powerful members of the Omegrion, must break the law of his people and the faith of his brothers to save the woman he loves. But the breech could very well spell the end of both their races and change their world forever.